How to reimburse medical expenses correctly according to tax principles - Sirirut Jaensirisak (Journal of Humanities and Social Sciences Mahasarakham University, 2021)
One element of organizational motivation is good welfare for employees and the welfare that every organization should consider providing for its employees is disbursement of medical expenseor This may include parents, spouses and children of the employee. This academic article aims to create an understanding of the organization and employees in providing welfare related to medical expenses, life insurance and health insurance including vaccination to prevent epidemic disease ; for example, COVID-19 by considering the maximum benefits that employees and the organization will receive in terms of taxes and duties under the revenue code. This paper studied and collected information from past research, relevant laws and discussed letters which involves medical welfare and other expenses mentioned above for the benefit of employees and the organization in terms of personal income tax and corporat iIncom income tax. In other words, medical income is exempt from personal income tax and employees are not required to be considered as assessable income under section 39 of the revenue code same as in organizations that provide welfare for employees can be treated as medical expenditures and also is not considered a prohibited expense under section 65 ter of the revenue code. Therefore, the organization needs to align medical welfare with the legal elements for the maximum benefit of taxation as follows. (1) The organization must define the reimbursement of medical expenses in the employee welfare regulations without discriminating against any person. (2) Employees must have evidence of medical expenses, such as receipts to prove that it has actually been paid and paid for it all, and (3) The organization must reimburse the employees for the medical expenses they actually paid on the basis of such evidencnd. Remember that, employee benefits of payment for health insurance in terms of corona- virus infection and vaccination fees for coronavirus infection are not considered a payment for medical treatment or vaccines for medical treatment. Therefore, it is not considered exempted income and employees have to take the benefits as assessable income subject to personal income tax. This does not include group insurance that the organization pays to employees, only for the portion that covers medical expenses. However, it does not include group insur- ance premiums that the organization pays to employees only for the portion that covers medical expenses, which is exempted from being regarded as the assessable income of the employee.